The Increase in Maternal Expression of axin1 and axin2 Contribute to the Zebrafish Mutant Ichabod Ventralized Phenotype. Issue 3 (March 2015) - Valenti, Fabio; Ibetti, Jessica; Komiya, Yuko; Baxter, Melissa; Lucchese, Anna Maria; Derstine, Lauren; Covaciu, Claudia; Rizzo, Valeria; Vento, Renza; Russo, Giuseppe; Macaluso, Marcella; Cotelli, Franco; et al.
ABSTRACT β‐catenin is a central effector of the Wnt pathway and one of the players in Ca+‐dependent cell‐cell adhesion. While many wnts are present and expressed in vertebrates, only one β‐catenin exists in the majority of the organisms. One intriguing exception is zebrafish that carries two genes for β‐catenin. The maternal recessive mutation ichabod presents very low levels of β‐catenin2 that in turn affects dorsal axis formation, suggesting that β‐catenin1 is incapable to compensate for β‐catenin2 loss and raising the question of whether these two β‐catenins may have differential roles during early axis specification. Here we identify a specific antibody that can discriminate selectively for β‐catenin1. By confocal co‐immunofluorescent analysis and low concentration gain‐of‐function experiments, we show that β‐catenin1 and 2 behave in similar modes in dorsal axis induction and cellular localization. Surprisingly, we also found that in the ich embryo the mRNAs of the components of β‐catenin regulatory pathway, including β‐catenin1, are more abundant than in the Wt embryo. Increased levels of β‐catenin1 are found at the membrane level but not in the nuclei till high stage. Finally, we present evidence that β‐catenin1 cannot revert the ich phenotype because it may be under the control of a GSK3β‐independent mechanism that required Axin's RGS domain function. J. Cell. Biochem. 116: 418–430, 2015. © 2014 Wiley Periodicals, Inc.